Quantitative thallium-201 myocardial exercise scintigraphy in normal subjects and patients with normal coronary arteries - Niemeyer, M.G.; Laarman, G.J.; Lelbach, S.; Cramer, M.J.; Go, L.T.; Verzijlbergen, J.F.; van der Wall, E.E.; Zwinderman, A.H.; Ascoop, C.A.P.L.; Pauwels, E.K.J. (European journal of radiology, 1990)
Quantitative thallium-201 myocardial exercise scintigraphy was tested in two patient populations representing alternative standards for cardiac normality: group I comprised 18 male uncatheterized patients with a low likelihood of coronary artery disease (CAD); group II contained 41 patients with normal coronary arteriograms. Group I patients were younger, they achieved a higher rate-pressure product than group II patients; all had normal findings by physical examination and electrocardiography at rest and exercise. Group II patients comprised 21 females, 11 patients showed abnormal electrocardiography at rest, and five patients showed ischemic ST depression during exercise. Twelve patients had signs of minimal CAD. Twelve patients revealed abnormal visual and quantitative thallium findings, three of these patients had minimal CAD. Profiles of uptake and washout of thallium-201 were derived from both patient groups, and compared with normal limits developed by Maddahi et al. Furthermore, low likelihood and angiographically normal patients may differ substantially, and both sets of normal patients should be considered when establishing criteria for abnormality in exercise thallium imaging. When commercial software containing normal limits for quantitative analysis of exercise thallium-201 imaging is used in clinical practice, it is mandatory to compare these with normal limits of uptake and washout of thallium-201, derived from the less heterogeneous group of low-likelihood subjects, which should be used in selecting a normal population to define normality.